PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR - Azwajum Muthohharah; Syamsuryani Eka Putri Atjo; Siti Raihan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) model in science and social studies learning for fourth-grade elementary school students. The research employed a Classroom Action Research (CAR) method using the Kemmis and Taggart model, which consists of four stages: planning, implementation, observation, and reflection. The study was conducted in two cycles, each consisting of two meetings. The research subjects were 14 fourth-grade students at SD Inpres Karamasa, Gowa Regency, consisting of 5 male students and 9 female students, along with one classroom teacher. Data collection techniques included observation, tests, and documentation. Data analysis was performed using qualitative and quantitative descriptive methods. The results showed that the application of the PBL model improved students' learning outcomes, as evidenced by increased teacher activity from 80% in cycle I to 93.3% in cycle II, and student activity from 67.6% in cycle I to 81.4% in cycle II. Student learning outcomes also improved, with the average score increasing from 75 in cycle I to 84.2 in cycle II, and learning mastery increasing from 64.29% in cycle I to 92.86% in cycle II. The learning process became more interactive, meaningful, and student-centered. Thus, it can be concluded that the application of the Problem Based Learning (PBL) model is effective in improving student learning outcomes in science and social studies learning for fourth-grade elementary school students.